Identification of polymorphism of FecX gene in indigenous sheep of Meghalaya - KHANIKAR, DIMPI; PHOOKAN, ARUNDHATI; KALITA, DHIRESWAR; ZAMAN, GALIB UZ; DAS, ARPANA; SAIKIA, DEEP PRAKASH; SARMA, MOMI (The Indian Journal of Animal Sciences, 2021)
Fecundity gene such as FecX, govern fertility and litter size in sheep. Selection of animals with the help of molecular markers through identification of polymorphism of fecundity genes is an impactful method of genetic improvement. The present study was carried out to identify the polymorphism of FecX gene in indigenous sheep of Meghalaya. Blood samples were collected from 50 randomly selected ewes from 2 districts of Meghalaya namely, East Khasi Hills and West Khasi Hills. Genomic DNA was extracted from the samples and PCR amplification of FecX gene with specific primer set was done. PCR product size of 141 bp was obtained. Further, digestion of the PCR product with restriction enzyme HinfI through PCR-RFLP technique was conducted to identify the variants in FecX gene. Upon digestion, 2 types of fragment pattern identified, arbitrarily designated as AA and AB genotype, where AA genotype yielded one fragment (141 bp) and AB genotype yielded 2 fragments (100 and 41 bp). Presence of polymorphism can be an important indicator for selection with the help of molecular markers.